Composite fluorescent material and preparation method thereof, perovskite-based composite light conversion film
By encapsulating and functionalizing perovskite quantum dots in Elosite nanotubes, the problems of perovskite materials in water and light-thermal resistance are solved, and ultra-stable fluorescence emission and efficient luminescence performance are achieved.
Patent Information
- Application Number
- CN202311557637.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-11-21
AI Technical Summary
The prior art is difficult to achieve large-scale preparation of perovskite composite photoconversion film materials with simple process, green and efficient, low-consumption and environmental protection.
Elosite nanotubes are used as matrix material, and perovskite quantum dots are encapsulated in their pipelines through halogen bonding, and selectively functionalized on the inner and outer surfaces of the pipelines to improve the material's water resistance, photothermal stability and luminescence performance.
The ultra-stable fluorescence emission of perovskite materials was achieved, and the stability was maintained in water for more than 49 days, and it still showed excellent luminescence performance after heating to 150°C and light.
Smart Images

Figure CN117987140B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of light conversion films, and in particular relates to a composite fluorescent material and a preparation method thereof, and an ultra-stable perovskite-based composite light conversion film comprising the composite fluorescent material. Background Art
[0002] All-inorganic cesium lead halide perovskite quantum dots have excellent optical properties such as high fluorescence quantum yield, narrow emission line and full visible light spectrum emission, and have broad application prospects in the fields of lighting and high-performance luminescent films. In recent years, the external quantum efficiency of luminescent materials based on perovskite quantum dots has been greatly improved. However, in terms of practical applications, there is still a big gap between the performance of perovskite-based luminescent materials and traditional rare earth luminescent materials. Among them, deep red light CsPbI3 and mixed halogen red light CsPb(Br / I)3 perovskite quantum dots are one of the necessary materials for realizing perovskite white light lighting and full-color display. In recent years, the use of organic small molecule ligands to passivate perovskite quantum dots to improve their luminescence performance and stability has received widespread attention. For example, Shi et al. proposed a strategy of using benzenesulfonate as an "equivalent halogen" anion to "kill three birds with one stone" and solve the above three problems at the same time. Through experimental and theoretical calculation analysis, it is known that benzenesulfonate can fill halogen vacancies and passivate surface defects. At the same time, due to the strong electron-withdrawing ability of sulfonate, a small amount of electrons will be transferred from perovskite to benzenesulfonate, reducing the "self-doping effect" of perovskite nanocrystals. In addition, benzenesulfonate can also increase the diffusion barrier of surface defects and inhibit the phase separation of CsPb(Br / I)3 nanocrystals. Cai et al. demonstrated efficient and stable red light emitting LEDs by doping poly(maleicanhydride-alt-1-octadecene) (PMA) in the synthesis of stable β-CsPbI3 nanocrystals. PMA can react with Pb through the O group in PMA. 2+ The coupling effect between them chemically reacts with PbI2 in the precursor, thereby promoting the crystallization of stable β-CsPbI3 NCs. At the same time, cross-linked PMA significantly reduces the PbCs anti-site defects on the surface of β-CsPbI3 NCs. Organic ligand passivated perovskite easily causes a large number of defects on the surface of CsPb(Br / I)3 quantum dots due to the shedding of ligands during the preparation and washing process. When these quantum dots are used in the field of luminescence, they will cause serious non-radiative recombination of carriers, shift of the luminescence peak of devices or thin films, and imbalance of electron and hole injection, which seriously affects the improvement of the luminescence efficiency of devices or thin films.
[0003] However, the synthesis of water-resistant, light-resistant and heat-resistant metal halide perovskite quantum dot composite film materials is still a major challenge in the field. How to achieve large-scale preparation of water-resistant, light-resistant and heat-resistant perovskite composite light conversion film materials with simple process, green efficiency, low consumption and environmental protection has always been a topic of concern in industry and academia worldwide. Summary of the invention
[0004] In order to solve the problems in the prior art, the present application provides a composite fluorescent material and a preparation method thereof, and an ultra-stable perovskite-based composite light conversion film comprising the composite fluorescent material of the present application. The composite fluorescent material of the present application effectively solves the problems of perovskite materials in terms of water resistance and light and heat resistance.
[0005] In a first aspect, the present application provides a composite fluorescent material, which includes halloysite nanotubes (HNTs) and cesium lead halide perovskite quantum dots encapsulated in the halloysite nanotubes.
[0006] In some embodiments, the inner surface of the halloysite nanotube is grafted with a halogen ligand represented by Formula I,
[0007]
[0008] In formula I, X1 is selected from chlorine, bromine or iodine, and R1 is selected from C1-C10 alkylene.
[0009] In some embodiments, R1 is selected from an alkylene group selected from C2-C6, such as ethylene, n-propylene, isopropylene, n-butylene, isobutylene, tert-butylene, n-pentylene, isopentylene, neopentylene, n-hexylene, 2-methylpentane, 3-methylpentane, and 2,2-dimethylbutane.
[0010] In some embodiments, the halogen ligand is selected from one or more of (3-bromopropyl)phosphoric acid, ethephon, 6-bromohexanephosphoric acid, and 4-bromobutanephosphoric acid.
[0011] In some embodiments, the outer surface of the halloysite nanotube is grafted with a fluorosilicone ligand represented by formula II,
[0012]
[0013] In formula II, R2, R3 and R4 are the same or different and are independently selected from C1-C6 alkyl, preferably C1-C4 alkyl, and R5 is selected from C1-C6 alkylene or fluorine-substituted C1-C6 alkylene.
[0014] In some embodiments, R2, R3 and R4 are the same or different and are independently selected from C1-C4 alkyl groups, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl or tert-butyl.
[0015] In some embodiments, R5 is selected from C1-C6 alkylene, such as methylene, ethylene, n-propylene, isopropylene, n-butylene, isobutylene, tert-butylene, n-pentylene, isopentylene, neopentylene, n-hexylene, 2-methylpentane, 3-methylpentane, 2,2-dimethylbutane. In some embodiments, R5 is selected from C1-C4 alkylene.
[0016] In some embodiments, R5 is selected from fluorine-substituted C1-C6 alkylene, such as fluorinated methylene, fluorinated ethylene, fluorinated n-propylene, fluorinated isopropylene, fluorinated n-butylene, fluorinated isobutylene, fluorinated tert-butylene, fluorinated n-pentylene, fluorinated isopentylene, fluorinated neopentylene, fluorinated n-hexylene, fluorinated 2-methylpentane, fluorinated 3-methylpentane, fluorinated 2,2-dimethylbutane. In some embodiments, R5 is selected from fluorinated C1-C4 alkylene.
[0017] In the present application, "fluoro" means that one or more hydrogen atoms in the substituent are replaced by fluorine atoms, such as monofluoro, difluoro, trifluoro, pentafluoro or heptafluoro.
[0018] In some embodiments, the fluorosiloxane ligand is selected from one or more of trifluoropropanetrimethoxysilane, triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane, 3,3,3-trifluoropropyltriethoxysilane, and (3,3,4,4,5,5,5-heptafluoropentyl)trimethoxysilane.
[0019] The inner and outer surfaces of the halloysite nanotubes of the present application are selectively functionalized, and the inner surface contains abundant halogen functional groups (including Cl, Br and I), which can form hydrogen bonds and coordination bonds with the halide anions and lead ions of the perovskite quantum dots; while the outer surface has strong hydrophobicity. Therefore, the halloysite nanotubes as a matrix material not only confine the encapsulation of the perovskite quantum dots, isolating the perovskite quantum dots from each other to reduce the quenching effect caused by aggregation, but also can passivate surface defects, thereby significantly improving the water resistance, light and heat stability and luminescence performance of the perovskite.
[0020] In some embodiments, the cesium lead halide perovskite quantum dots are selected from CsPbCl3 perovskite quantum dots, CsPbBr3 perovskite quantum dots, CsPbI3 perovskite quantum dots, CsPbCl 1.5 Br 1.5 Perovskite quantum dots, CsPbCl 1.5 I 1.5 Perovskite quantum dots and CsPbBr 1.5 I 1.5 One or more of perovskite quantum dots.
[0021] In some embodiments, the mass ratio of the cesium lead halide perovskite quantum dots to the halloysite nanotubes is (0.1-0.5):1, for example, 0.13:1, 0.15:1, 0.17:1, 0.2:1, 0.23:1, 0.25:1, 0.27:1, 0.3:1, 0.33:1, 0.35:1, 0.37:1, 0.4:1, 0.43:1, 0.45:1, 0.47:1 or any value therebetween. In some embodiments, the mass ratio of the cesium lead halide perovskite quantum dots to the halloysite nanotubes is (0.15-0.3):1.
[0022] In a second aspect, the present application provides a method for preparing a composite fluorescent material, which comprises the following steps:
[0023] S1: performing a third reaction on the halloysite nanotubes and the lead halide to obtain a third reaction product,
[0024] S2: performing a fourth reaction on the third reaction product of step S1 and the cesium oleate solution to obtain the composite fluorescent material.
[0025] In some embodiments, the halloysite nanotubes are selected from the group consisting of halloysite nanotubes HNT-XF modified with halogen ligands and fluorosilicone ligands.
[0026] In some embodiments, the preparation of the halloysite nanotube HNT-XF comprises the following steps:
[0027] Step A: performing a first reaction on the halloysite nanotube and the halogen ligand shown in Formula I to obtain the halloysite nanotube HNT-X modified with the halogen ligand;
[0028] Step B: subjecting the halloysite nanotube HNT-X prepared in step A to a second reaction with a fluorosiloxane ligand shown in formula II to obtain a halloysite nanotube HNT-XF modified with a halogen ligand and a fluorosiloxane ligand;
[0029]
[0030] In formula I, X1 is selected from chlorine, bromine or iodine, and R1 is selected from C1-C10 alkylene;
[0031]
[0032] In formula II, R2, R3 and R4 are the same or different and are independently selected from C1-C6 alkyl groups, and R4 is selected from C1-C6 alkylene groups or fluorine-substituted C1-C6 alkylene groups.
[0033] In some embodiments, in Formula I, R1 is selected from an alkylene group selected from C2-C6, such as ethylene, n-propylene, isopropylene, n-butylene, isobutylene, tert-butylene, n-pentylene, isopentylene, neopentylene, n-hexylene, 2-methylpentane, 3-methylpentane, and 2,2-dimethylbutane.
[0034] In some embodiments, in Formula II, R2, R3 and R4 are the same or different and are independently selected from C1-C4 alkyl groups, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl or tert-butyl.
[0035] In some embodiments, in formula II, R5 is selected from C1-C6 alkylene, such as methylene, ethylene, n-propylene, isopropylene, n-butylene, isobutylene, tert-butylene, n-pentylene, isopentylene, neopentylene, n-hexylene, 2-methylpentane, 3-methylpentane, 2,2-dimethylbutane. In some embodiments, R5 is selected from C1-C4 alkylene.
[0036] In some embodiments, in formula II, R5 is selected from fluorine-substituted C1-C6 alkylene, such as fluorinated methylene, fluorinated ethylene, fluorinated n-propylene, fluorinated isopropylene, fluorinated n-butylene, fluorinated isobutylene, fluorinated tert-butylene, fluorinated n-pentylene, fluorinated isopentylene, fluorinated neopentylene, fluorinated n-hexylene, fluorinated 2-methylpentane, fluorinated 3-methylpentane, fluorinated 2,2-dimethylbutane. In some embodiments, R5 is selected from fluorinated C1-C4 alkylene.
[0037] In some embodiments, the halogen ligand is selected from one or more of (3-bromopropyl)phosphoric acid, ethephon, 6-bromohexanephosphoric acid, and 4-bromobutanephosphoric acid.
[0038] In some embodiments, the fluorosiloxane ligand is selected from one or more of trifluoropropanetrimethoxysilane, triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane, 3,3,3-trifluoropropyltriethoxysilane, and (3,3,4,4,5,5,5-heptafluoropentyl)trimethoxysilane.
[0039] The preparation method of the present application encapsulates perovskite quantum dots in the tube of halloysite nanotubes through halogen bonding. The inner and outer surfaces of the tube of the halloysite nanotube are selectively functionalized, and the inner surface contains rich halogen functional groups (including Cl, Br and I), which can form hydrogen bonds and coordination bonds with the halide anions and lead ions of the perovskite quantum dots; while the outer surface has strong hydrophobicity. Therefore, halloysite nanotubes as matrix materials not only confine the encapsulation of perovskite quantum dots, isolating the perovskite quantum dots from each other to reduce the quenching effect caused by aggregation, but also can significantly improve the water resistance, light and heat stability and luminescence performance of perovskite by passivating surface defects.
[0040] In some embodiments, the halloysite-perovskite composite material (composite fluorescent material) prepared by the preparation method of the present application exhibits ultra-stable fluorescent emission for more than 49 days in water, and still exhibits excellent luminescent properties after being heated to 150°C and illuminated. This technology will provide a new design strategy for the field of light-emitting diodes and light-conversion films.
[0041] In some embodiments, in step S1, the lead halide is selected from one or more of PbCl2, PbBr2 and PbI2.
[0042] In some embodiments, in step S1, the ratio of the mass of the halloysite nanotubes to the molar amount of the lead halide is (0.01-0.5) g:1mmol, for example, 0.03g:1mmol, 0.05g:1mmol, 0.07g:1mmol, 0.1g:1mmol, 0.13g:1mmol, 0.15g:1mmol, 0.17g:1mmol, 0.2g:1mmol, 0.23g:1mmol, 0.25g:1mmol, 0.27g:1mmol, 0.3g:1mmol, 0.33g:1mmol, 0.35g:1mmol, 0.37g:1mmol, 0.3g:1mmol, 0.43g:1mmol, 0.45g:1mmol, 0.47g:1mmol or any value therebetween. In some embodiments, the ratio of the mass of the halloysite nanotubes to the molar amount of the lead halide is (0.04-0.4) g:1 mmol.
[0043] In some embodiments, in step S1, the third reaction is carried out in a mixed solvent of dimethyl sulfoxide and anhydrous ethanol. In some embodiments, in step S1, the volume ratio of dimethyl sulfoxide to anhydrous ethanol is (1-2):1.
[0044] In some embodiments, in step S2, the ratio of the mass of the third reaction product to the molar amount of cesium oleate in the cesium oleate solution is (0.1-3) g:1mmol, for example, 0.1 g:1mmol, 0.2 g:1mmol, 0.3 g:1mmol, 0.4 g:1mmol, 0.5 g:1mmol, 0.6 g:1mmol, 0.7 g:1mmol, 0.8 g:1mmol, 0.9 g:1mmol, 1 g:1mmol, 1.3 g:1mmol, 1.5 g:1mmol, 1.7 g:1mmol, 2 g:1mmol, 2.3 g:1mmol, 2.5 g:1mmol, 2.7 g:1mmol or any value therebetween. In some embodiments, the ratio of the mass of the third reaction product to the molar amount of cesium oleate in the cesium oleate solution is (0.25-1) g:1mmol.
[0045] In some embodiments, in step S2, the solvent in the cesium oleate solution is selected from a mixed solvent of dimethyl sulfoxide and anhydrous ethanol. Preferably, the volume ratio of dimethyl sulfoxide to anhydrous ethanol is (1-2):1.
[0046] In some embodiments, in step S2, the molar concentration of cesium oleate in the cesium oleate solution is 50 mM-100 mM, for example, 60 mM, 70 mM, 80 mM or 90 mM.
[0047] In some embodiments, in step S2, the fourth reaction is carried out in toluene solvent.
[0048] In some embodiments, in step A, the ratio of the mass of the halloysite nanotubes to the molar amount of the halogen ligand is (100-1000) mg:1mmol, for example, 150 mg:1mmol, 200 mg:1mmol, 250 mg:1mmol, 300 mg:1mmol, 350 mg:1mmol, 400 mg:1mmol, 450 mg:1mmol, 500 mg:1mmol, 550 mg:1mmol, 600 mg:1mmol, 650 mg:1mmol, 700 mg:1mmol, 750 mg:1mmol, 800 mg:1mmol, 850 mg:1mmol, 900 mg:1mmol or any value therebetween. In some embodiments, in step A, the ratio of the mass of the halloysite nanotubes to the molar amount of the halogen ligand is (200-500) mg:1mmol.
[0049] In some embodiments, in step A, the first reaction is carried out in a mixed solvent of anhydrous ethanol and water. In some embodiments, in step A, the volume ratio of anhydrous ethanol to water is 2:1.
[0050] In some embodiments, in step A, the temperature of the first reaction is 5°C-35°C.
[0051] In some embodiments, in step A, the first reaction time is 5 days to 9 days.
[0052] In some embodiments, in step B, the ratio of the mass of the halloysite nanotube HNT-X to the molar amount of the fluorosilicone ligand is (0.01-10) g:1 mmol, for example, 0.05 g:1 mmol, 0.1 g:1 mmol, 0.5 g:1 mmol, 1 g:1 mmol, 1.5 g:1 mmol, 2 g:1 mmol, 2.5 g:1 mmol, 3 g:1 mmol, 3.5 g:1 mmol, 4 g:1 mmol, 4.5 g:1 mmol, 5 g:1 mmol, 5.5 g:1 mmol, 6 g:1 mmol, 6.5 g:1 mmol, 7 g:1 mmol, 7.5 g:1 mmol, 8 g:1 mmol, 8.5 g:1 mmol, 9 g:1 mmol, 9.5 g:1 mmol or any value therebetween.
[0053] In some embodiments, in step B, the second reaction is carried out in toluene solvent.
[0054] In some embodiments, in step B, the temperature of the second reaction is 60°C-100°C.
[0055] In some embodiments, in step B, the time of the second reaction is 12h-36h.
[0056] In some embodiments, the preparation method of cesium oleate is as follows:
[0057] Take oleic acid (OA) and octadecene (ODE) at a volume ratio of 1:(2-4), mix well, and obtain a first mixed solvent; add cesium salt and ligand to the first mixed solvent at a ratio of 2.5-5.0mmol cesium salt and 1-2.5mmol ligand to 100mL of the first mixed solvent, heat to 120-150℃ under nitrogen atmosphere to completely dissolve the cesium salt, and keep warm for 1-2h to evaporate the low boiling point solvent (the low boiling point solvent is the impurity solvent in the produced oleic acid and octadecene), then heat to 150-180℃, carry out coordination exchange reaction for 1-2.5h, and after the reaction is complete, cool naturally to room temperature to obtain brown waxy solid cesium oleate.
[0058] In some embodiments, the cesium salt is one or more of cesium carbonate, cesium bromide, cesium sulfate, cesium acetate or cesium chloride.
[0059] In some embodiments, the ligand is one or more of oleylamine or octadecylamine.
[0060] In some embodiments, the method for preparing the composite fluorescent material comprises the following steps:
[0061] Step 1: performing a first reaction between the halloysite nanotube and the halogen ligand to obtain the halloysite nanotube HNT-X modified with the halogen ligand;
[0062] Step 2: subjecting the halloysite nanotube HNT-X prepared in step 1 to a second reaction with a fluorosiloxane ligand to obtain a halloysite nanotube HNT-XF modified with a halogen ligand and a fluorosiloxane ligand;
[0063] Step 3: performing a third reaction on the halloysite nanotube HNT-XF in step 2 and lead halide to obtain a third reaction product;
[0064] Step 4: performing a fourth reaction on the third reaction product of step 4 and a cesium oleate solution to obtain the composite fluorescent material;
[0065] Among them, the halogen ligand and fluorosilicone ligand, reaction conditions, and ratio of each reactant in step 1 and step 2 are the same as those in step A and step B, and the lead halide, cesium oleate, reaction conditions, and ratio of each reactant in step 3 and step 4 are the same as those in step S1 and step S2.
[0066] In some embodiments, the method for preparing the composite fluorescent material comprises the following specific steps:
[0067] 1) Selective functionalization of the inner surface of halloysite nanotubes (HNTs):
[0068] Anhydrous ethanol and deionized water were taken at a volume ratio of 2:1, respectively, and mixed to obtain a second mixed solvent; 100 mg of HNT and 0.4 mmol of halogen ligand were added to 100 mL of the second mixed solvent, and then the pH value of the above system was adjusted to about 4, and the halogen ligand solution was adsorbed into the inner cavity of HNT by a vacuum-assisted method. After stirring and reacting at room temperature for one week, the HNT was washed three times with the second mixed solvent, and dried at 100°C to obtain halogen ligand-modified HNT, which was recorded as HNT-X (X = Cl, Br, I);
[0069] Preferably, the halogen ligand is one or more of (3-bromopropyl)phosphoric acid, ethephon, 6-bromohexanephosphoric acid, and 4-bromobutanephosphoric acid.
[0070] 2) Modification of the hydrophobic layer on the outer surface of halloysite nanotubes (HNTs):
[0071] 0.1-1.0 mmol of fluorosilicone ligand and 0.1-1.0 g of HNT-X were added to 80 mL of dry toluene solvent, and the dry toluene solvent, fluorosilicone ligand and HNT-X were taken respectively. The suspension was ultrasonically dispersed at room temperature for 20 min, and then stirred and heated at 80° C. for 24 h. When the reaction temperature dropped to room temperature, it was washed with toluene three times, and dried in vacuum at 100° C. to obtain a superhydrophobic HNT-XF matrix material;
[0072] Preferably, the fluorosiloxane ligand is one or more of trifluoropropanetrimethoxysilane, triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane, 3,3,3-trifluoropropyltriethoxysilane, and (3,3,4,4,5,5,5-heptafluoropentyl)trimethoxysilane.
[0073] 3) Preparation of Halloysite-Lead Halide Perovskite Composite Material (Composite Fluorescent Material):
[0074] Dimethyl sulfoxide and anhydrous ethanol are taken at a volume ratio of 1 to 2:1, respectively, and mixed to obtain a second mixed solvent; 0.5 to 2.5 mmol of lead halide (PbX2, wherein X = Cl, Br, I) is added to 10 mL of the second mixed solvent, and the second mixed solvent and lead halide are taken respectively; the lead halide is added to the second mixed solvent, and magnetic stirring is performed to completely dissolve the lead halide to obtain a mixed solution; 1.0 to 2.0 g of HNT-XF is added to 100 mL of the mixed solution, and HNT-XF is added to the mixed solution, and after ultrasonication for 5 hours, the temperature is raised to 120°C until it is completely dried, so that the lead halide is encapsulated in the tube of HNT-XF to obtain a product, and the product is washed with the second mixed solvent at least three times to obtain PbX2@HNT-XF material. Subsequently, cesium oleate is added to the second mixed solvent, and magnetic stirring is performed to completely dissolve the cesium oleate to obtain a cesium oleate solution with a molar concentration of 50 to 100 mM; according to the ratio of 10 to 20 mL of cesium oleate solution and 0.5 to 1.0 g of PbX2@HNT-XF material required for 100 mL of anhydrous toluene, anhydrous toluene, cesium oleate solution and PbX2@HNT-XF material are taken respectively, and the PbX2@HNT-XF material is dispersed in the cesium oleate solution, magnetically stirred for 1 to 5 hours, and then added to anhydrous toluene, and magnetically stirred for another 0.5 to 1 hour, filtered, separated, washed, and dried to obtain a water-resistant and light-heat-resistant halloysite-perovskite (CsPbX3@HNT-XF) composite material;
[0075] Preferably, PbX2 is one or two of PbCl2, PbBr2, and PbI2; when two PbX2 are used, the molar ratio of the two lead halides is 1:1.
[0076] In a third aspect, the present application provides the use of the composite fluorescent material described in the first aspect or the composite fluorescent material prepared by the preparation method described in the second aspect in a light emitting diode or a light conversion film.
[0077] In a fourth aspect, the present application provides a perovskite-based composite light conversion film, which includes the composite fluorescent material described in the first aspect or the composite fluorescent material prepared by the preparation method described in the second aspect.
[0078] In some embodiments, the perovskite-based composite light conversion film further comprises a polymer, and the mass ratio of the composite fluorescent material to the polymer is 1:(10-200), for example, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110, 1:120, 1:130, 1:140, 1:150, 1:160, 1:170, 1:180, 1:190 or any value therebetween. In some embodiments, the mass ratio of the composite fluorescent material to the polymer is 1:(50-100).
[0079] In some embodiments, the polymer is selected from polystyrene and / or polysulfone.
[0080] In some embodiments, the method for preparing the perovskite-based composite light conversion film comprises the following steps:
[0081] Step M1: mixing a polymer with a solvent to obtain a polymer solution, preferably, the polymer is selected from polystyrene and / or polysulfone, preferably, the solvent is selected from toluene, and preferably, the volume ratio of the solvent to the mass ratio of the polymer satisfies (5-20) mL:1 g;
[0082] Step M2: mixing the composite fluorescent material with the polymer solution of step M1 to obtain a mixed solution. Preferably, the mass ratio of the composite fluorescent material to the polymer in the polymer solution is 1:(10-200), for example, 1:(50-100);
[0083] Step M3: The mixed solution of step M2 is subjected to a film-forming method such as a Meyer rod coating method to prepare the perovskite-based composite light conversion film material.
[0084] In some embodiments, the method for preparing the perovskite-based composite light conversion film comprises the following specific steps:
[0085] Toluene and polymer are taken at a volume (mL) and mass (g) ratio of 5 to 20:1, mixed, and magnetically stirred to completely dissolve the polymer to obtain a polymer solution; polymer solution and composite fluorescent material are taken at a ratio of 0.5 to 1.0 g of composite fluorescent material (such as CsPbX3@HNT-XF material) per 100 mL of polymer solution, and the composite fluorescent material is dispersed in the polymer solution. After magnetic stirring for 6 to 12 hours, a water-resistant, light-resistant and heat-resistant perovskite-based composite light conversion film material is prepared using a Myler rod coating technique.
[0086] Compared with the prior art, the beneficial effects of this application are:
[0087] The preparation method of the present application uses natural halloysite nanotubes as the matrix material. The process is simple, green and efficient, low-consumption, environmentally friendly and green and efficient. It is a key technology to solve the problems of water resistance and light and heat resistance of perovskite materials. It also provides new ideas for the industrial application of perovskite materials (in the field of light-emitting diodes and light conversion films), and has important theoretical significance and practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0088] Figure 1 It is a schematic diagram of a preparation method for a perovskite-based composite light conversion film according to some implementation methods of the present application.
[0089] Figure 2 This is a physical characterization diagram of the perovskite-based composite light conversion film prepared in Example 2.
[0090] Figure 3 It is a fluorescence test chart and a color gamut coordinate chart of the perovskite-based composite light conversion film prepared in Example 2.
[0091] Figure 4 It is an overlapping diagram of the fluorescence image of the perovskite-based composite light conversion film prepared in Example 2 and Example 4 and the plant chlorophyll and photosynthetic system reaction center.
[0092] Figure 5 The chlorophyll content of the perovskite-based composite light conversion film obtained in Example 2 and Example 4 after irradiating the plant. Among them, Red is Example 2, and Blue is Example 4.
[0093] Figure 6 The thermal stability and water stability of the perovskite-based composite light conversion film prepared in Example 2 are shown. DETAILED DESCRIPTION
[0094] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0095] Example 1
[0096] Take oleic acid and octadecene at a volume ratio of 1:2, mix well, and obtain the first mixed solvent. Add 2.5mmol cesium carbonate and 1mmol oleylamine to 100mL of the first mixed solvent, heat to 120℃ under nitrogen atmosphere to completely dissolve cesium carbonate, and keep warm for 2h to evaporate the low boiling point solvent. Heat to 150℃ again, and carry out coordination exchange reaction for 2.5h. After the reaction is complete, cool naturally to room temperature to obtain brown waxy solid cesium oleate.
[0097] Anhydrous ethanol and deionized water were taken at a volume ratio of 2:1, respectively, and mixed to obtain a second mixed solvent. 100 mg of HNT (halloysite nanotubes) and 0.4 mmol of (3-bromopropyl) phosphoric acid were added to 100 mL of the second mixed solvent, and then the pH value of the above system was adjusted to about 4. The (3-bromopropyl) phosphoric acid solution was adsorbed into the inner cavity of the HNT by a vacuum-assisted method. After stirring and reacting at room temperature for one week, the HNT was washed three times with the second mixed solvent and dried at 100°C to obtain (3-bromopropyl) phosphoric acid-modified HNT, which was recorded as HNT-Br.
[0098] 0.1 mmol of trifluoropropane trimethoxysilane and 0.1 g of HNT-Br were added to 80 mL of dry toluene solvent, and the mixture was ultrasonically dispersed at room temperature for 20 min, and then stirred and heated at 80 °C for 24 h. When the reaction temperature dropped to room temperature, the mixture was washed three times with toluene and dried in vacuo at 100 °C to obtain a superhydrophobic HNT-Br-F matrix material.
[0099] Dimethyl sulfoxide and anhydrous ethanol were taken at a volume ratio of 1:1, mixed to obtain a third mixed solvent; the third mixed solvent and lead bromide were taken at a ratio of 0.5mmol lead bromide added to 10mL of the third mixed solvent; lead bromide was added to the third mixed solvent, magnetic stirring was applied to completely dissolve the lead bromide, and a mixed solution was obtained. HNT-Br-F was added to the mixed solution at a ratio of 1.0g HNT-Br-F added to 100mL of the mixed solution, and the temperature was raised to 120°C after ultrasonic treatment for 5h until it was completely dried, so that the lead bromide was encapsulated in the tube of HNT-Br-F to obtain a product, and the product was washed at least three times with the third mixed solvent to obtain PbBr2@HNT-Br-F material. Subsequently, cesium oleate was added to the third mixed solvent, magnetic stirring was applied to completely dissolve the cesium oleate, and a cesium oleate solution with a molar concentration of 50mM was obtained. According to the ratio of 10 mL of cesium oleate solution and 0.5 g of PbBr2@HNT-Br-F material to 100 mL of anhydrous toluene, anhydrous toluene, cesium oleate solution and PbBr2@HNT-Br-F material were taken respectively, and the PbBr2@HNT-Br-F material was dispersed in the cesium oleate solution. After magnetic stirring for 1 hour, it was added into anhydrous toluene and magnetically stirred for another 0.5 hour. The material was separated by suction filtration, washed and dried to obtain a water-resistant and light-heat-resistant halloysite-perovskite (CsPbBr3@HNT-Br-F) composite material, wherein 0.18 g of CsPbBr3 perovskite quantum dots were encapsulated in the composite material based on 1 g of halloysite nanotubes.
[0100] Toluene and polystyrene were taken at a volume (mL) and mass (g) ratio of 10:1, mixed, and magnetically stirred to completely dissolve the polystyrene to obtain a polystyrene solution. Polystyrene solution and CsPbBr3@HNT-Br-F were taken at a ratio of 0.1gCsPbBr3@HNT-Br-F material per 100mL polystyrene solution. CsPbBr3@HNT-Br-F material was dispersed in the polystyrene solution, magnetically stirred for 6-12h, and then a water-resistant and light-heat-resistant perovskite-based composite light conversion film was prepared using the Myler rod coating technology.
[0101] Example 2
[0102] Take oleic acid and octadecene at a volume ratio of 1:3, mix well, and obtain the first mixed solvent. Add 2.5mmol cesium carbonate and 1mmol oleylamine to 100mL of the first mixed solvent, heat to 120℃ under nitrogen atmosphere to completely dissolve cesium carbonate, and keep warm for 2h to evaporate the low boiling point solvent. Heat to 150℃ again, and perform coordination exchange reaction for 2.5h. After the reaction is complete, cool naturally to room temperature to obtain brown waxy solid cesium oleate.
[0103] Anhydrous ethanol and deionized water were taken at a volume ratio of 2:1, respectively, and mixed to obtain a second mixed solvent. 200 mg of HNT and 0.4 mmol of ethephon were added to 100 mL of the second mixed solvent, and then the pH value of the above system was adjusted to about 4. The ethephon solution was adsorbed into the inner cavity of the HNT by a vacuum-assisted method. After stirring and reacting at room temperature for one week, the HNT was washed three times with the second mixed solvent and dried at 100°C to obtain ethephon-modified HNT, which was recorded as HNT-Cl.
[0104] 0.1 mmol of trifluoropropane trimethoxysilane and 0.1 g of HNT-Cl were added to 80 mL of dry toluene solvent, and the mixture was ultrasonically dispersed at room temperature for 20 min, and then stirred and heated at 80 °C for 24 h. When the reaction temperature dropped to room temperature, the mixture was washed three times with toluene and dried in vacuo at 100 °C to obtain a superhydrophobic HNT-Cl-F matrix material.
[0105] Dimethyl sulfoxide and anhydrous ethanol were taken at a volume ratio of 1:1, and mixed to obtain a third mixed solvent. The third mixed solvent and lead iodide were taken at a ratio of 0.5mmol lead iodide added to 10mL of the third mixed solvent; lead iodide was added to the third mixed solvent, and magnetic stirring was performed to completely dissolve the lead iodide to obtain a mixed solution. HNT-Cl-F was added to the mixed solution at a ratio of 1.0g HNT-Cl-F added to 100mL of the mixed solution, and the temperature was raised to 120°C after ultrasonic treatment for 5h until it was completely dried, so that the lead iodide was encapsulated in the tube of HNT-Cl-F to obtain a product, and the product was washed with the third mixed solvent at least three times to obtain PbI2@HNT-Cl-F material. Subsequently, cesium oleate was added to the third mixed solvent, and magnetic stirring was performed to completely dissolve the cesium oleate to obtain a cesium oleate solution with a molar concentration of 50mM. According to the ratio of 100 mL of anhydrous toluene to 10 mL of cesium oleate solution and 0.5 g of PbI2@HNT-Cl-F material, anhydrous toluene, cesium oleate solution and PbI2@HNT-Cl-F material were taken respectively. PbI2@HNT-Cl-F material was dispersed in cesium oleate solution, magnetically stirred for 1 hour, added into anhydrous toluene, magnetically stirred for another 0.5 hour, filtered, separated, washed and dried to obtain a water-resistant and light-heat-resistant halloysite-perovskite (CsPbI3@HNT-Cl-F) composite material, wherein 0.20 g of CsPbI3 perovskite quantum dots were encapsulated in the composite material based on 1 g of halloysite nanotubes.
[0106] Toluene and polystyrene were taken at a volume (mL) and mass (g) ratio of 10:1, mixed, and magnetically stirred to completely dissolve the polystyrene to obtain a polystyrene solution. Polystyrene solution and CsPbI3@HNT-Cl-F were taken at a ratio of 0.1gCsPbI3@HNT-Cl-F material per 100mL polystyrene solution. CsPbBr3@HNT-Br-F material was dispersed in the polystyrene solution, and after magnetic stirring for 6-12h, a water-resistant and light-heat-resistant perovskite-based composite light conversion film was prepared using the Myler rod coating technology.
[0107] The electron microscope images of the halloysite-perovskite composite material and the perovskite-based composite light conversion film prepared in this embodiment are as follows: Figure 2 As shown, from Figure 2 It can be seen from a that the HNT material has a clear tubular structure. Figure 2 In b, it can be seen that the perovskite quantum dots are encapsulated in the halloysite nanotubes.
[0108] The fluorescence test graph and color gamut coordinate graph of the halloysite-perovskite composite material prepared in this embodiment are shown in Figure 3 As shown, from Figure 3 It can be seen that its fluorescent emission range has a wider color gamut range than that of the National Television Standards Committee.
[0109] The fluorescence image of the perovskite-based composite light conversion film prepared in this embodiment and the overlapping image of the plant chlorophyll and photosynthetic system reaction center are shown in FIG. Figure 4 As shown, from Figure 4 It can be seen from b that it has a good overlap with the absorption of chlorophyll and photosynthetic system reaction center of plants, so it can be used as a light conversion film for plant photosynthesis.
[0110] The perovskite-based composite light conversion film prepared in this embodiment has an effect on the chlorophyll content of plants after irradiation. Figure 5 As shown, from Figure 5 It can be seen that the plants irradiated by the perovskite-based composite light conversion film have a higher chlorophyll content, indicating that the light conversion film material is beneficial to promoting plant photosynthesis.
[0111] The thermal stability and water stability test results of the perovskite-based composite light conversion film prepared in this embodiment are as follows: Figure 6 As shown, from Figure 6 It can be seen that the perovskite-based composite light conversion film prepared in the example exhibits ultra-stable fluorescence emission for more than 49 days in water ( Figure 6 a), still exhibits excellent luminescence properties after heating to 150°C and irradiation ( Figure 6 b).
[0112] Example 3
[0113] Oleic acid and octadecene were taken at a volume ratio of 1:2, mixed, and the first mixed solvent was obtained. 2.5mmol cesium carbonate and 1mmol oleylamine were added to 100mL of the first mixed solvent, and the temperature was raised to 120°C under a nitrogen atmosphere to completely dissolve the cesium carbonate, and the temperature was kept for 2h to evaporate the low boiling point solvent, and then heated to 150°C for 2.5h of coordination exchange reaction. After the reaction was complete, it was naturally cooled to room temperature to obtain brown waxy solid cesium oleate.
[0114] Anhydrous ethanol and deionized water were taken at a volume ratio of 2:1, respectively, and mixed to obtain a second mixed solvent. 100 mg of HNT and 0.4 mmol of 6-bromohexane phosphate were added to 100 mL of the second mixed solvent, and then the pH value of the above system was adjusted to about 4. The 6-bromohexane phosphate solution was adsorbed into the HNT cavity by a vacuum-assisted method. After stirring and reacting at room temperature for one week, it was washed three times with the second mixed solvent and dried at 100°C to obtain 6-bromohexane phosphate-modified HNT, which was recorded as HNT-Br.
[0115] 0.1 mmol of trifluoropropane trimethoxysilane and 0.1 g of HNT-Br were added to 80 mL of dry toluene solvent, and the mixture was ultrasonically dispersed at room temperature for 20 min, and then stirred and heated at 80 °C for 24 h. When the reaction temperature dropped to room temperature, the mixture was washed three times with toluene and dried in vacuo at 100 °C to obtain a superhydrophobic HNT-Br-F matrix material.
[0116] Dimethyl sulfoxide and anhydrous ethanol were taken at a volume ratio of 1:1, and mixed to obtain a third mixed solvent. The third mixed solvent and lead chloride were taken at a ratio of 0.5mmol lead chloride added to 10mL of the third mixed solvent. Lead chloride was added to the third mixed solvent, and magnetic stirring was performed to completely dissolve the lead chloride to obtain a mixed solution. HNT-Br-F was added to the mixed solution at a ratio of 1.0g HNT-Br-F added to 100mL of the mixed solution, and the temperature was raised to 120°C after ultrasonic treatment for 5h until it was completely dried, so that the lead chloride was encapsulated in the tube of HNT-Br-F to obtain a product, and the product was washed at least three times with the third mixed solvent to obtain PbCl2@HNT-Br-F material. Subsequently, cesium oleate was added to the third mixed solvent, and magnetic stirring was performed to completely dissolve the cesium oleate to obtain a cesium oleate solution with a molar concentration of 50mM. According to the ratio of 10 mL of cesium oleate solution and 0.5 g of PbCl2@HNT-Br-F material to 100 mL of anhydrous toluene, anhydrous toluene, cesium oleate solution and PbCl2@HNT-Br-F material were taken respectively, and the PbCl2@HNT-Br-F material was dispersed in the cesium oleate solution. After magnetic stirring for 1 hour, it was added into anhydrous toluene and magnetically stirred for another 0.5 hour. The material was separated by suction filtration, washed and dried to obtain a water-resistant and light-heat-resistant halloysite-perovskite (CsPbCl3@HNT-Br-F) composite material, wherein 0.17 g of CsPbCl3 perovskite quantum dots were encapsulated in the composite material based on 1 g of halloysite nanotubes.
[0117] Toluene and polysulfone were taken at a volume (mL) and mass (g) ratio of 10:1, mixed, and magnetically stirred to completely dissolve the polysulfone to obtain a polysulfone solution. Polysulfone solution and CsPbCl3@HNT-Br-F were taken at a ratio of 0.1g CsPbCl3@HNT-Br-F material per 100mL polysulfone solution. CsPbCl3@HNT-Br-F material was dispersed in the polysulfone solution, magnetically stirred for 6-12h, and then a water-resistant and light-heat-resistant perovskite-based composite light conversion film was prepared using the Myler rod coating technology.
[0118] Example 4
[0119] Take oleic acid and octadecene at a volume ratio of 1:2, mix well, and obtain the first mixed solvent. Add 2.5mmol cesium carbonate and 1mmol oleylamine to 100mL of the first mixed solvent, heat to 120℃ under nitrogen atmosphere to completely dissolve cesium carbonate, and keep warm for 2h to evaporate the low boiling point solvent. Heat to 150℃ again, and carry out coordination exchange reaction for 2.5h. After the reaction is complete, cool naturally to room temperature to obtain brown waxy solid cesium oleate.
[0120] 0.1 mmol trifluoropropane trimethoxysilane and 0.1 g HNT were added to 80 mL dry toluene solvent, and ultrasonic dispersion was performed at room temperature for 20 min. The mixture was heated and stirred at 80 °C for 24 h. When the reaction temperature dropped to room temperature, the mixture was washed three times with toluene and dried in vacuo at 100 °C to obtain a superhydrophobic HNT-F matrix material.
[0121] Anhydrous ethanol and deionized water were taken at a volume ratio of 2:1, respectively, and mixed to obtain a second mixed solvent. 100 mg of HNT and 0.4 mmol of 6-bromohexane phosphate were added to 100 mL of the second mixed solvent, and then the pH value of the above system was adjusted to about 4. The 6-bromohexane phosphate solution was adsorbed into the HNT cavity by a vacuum-assisted method. After stirring and reacting at room temperature for one week, it was washed three times with the second mixed solvent and dried at 100°C to obtain 6-bromohexane phosphate-modified HNT, which was recorded as HNT-Br.
[0122] Take dimethyl sulfoxide and anhydrous ethanol at a volume ratio of 1:1, mix them, and obtain a third mixed solvent; add 0.25mmol lead chloride and 0.25mmol lead bromide to 10mL of the third mixed solvent, take the third mixed solvent, lead chloride and lead bromide respectively; add lead chloride and lead bromide to the third mixed solvent, stir magnetically, and completely dissolve lead chloride and lead bromide to obtain a mixed solution. Add 1.0g HNT-Br-F to 100mL of the mixed solution, add HNT-Br-F to the mixed solution, ultrasonicate for 5h, heat to 120℃ until completely dry, and encapsulate lead chloride and lead bromide in the tube of HNT-Br-F to obtain the product, wash the product with the third mixed solvent at least three times, and obtain PbCl 0.5 Br 0.5 @HNT-Br-F material. Subsequently, cesium oleate was added to the third mixed solvent and magnetically stirred to completely dissolve the cesium oleate to obtain a cesium oleate solution with a molar concentration of 50 mM. 100 mL of anhydrous toluene requires 10 mL of cesium oleate solution and 0.5 g of PbCl 0.5 Br 0.5 @HNT-Br-F material ratio, take anhydrous toluene, cesium oleate solution and PbCl 0.5 Br 0.5 @HNT-Br-F material, PbCl 0.5 Br 0.5 The HNT-Br-F material was dispersed in a cesium oleate solution, magnetically stirred for 1 h, added to anhydrous toluene, and magnetically stirred for another 0.5 h. The product was separated by filtration, washed, and dried to obtain water-resistant and light-resistant halloysite-perovskite (Cs PbCl 1.5 Br 1.5 @HNT-Br-F) composite material, wherein, based on 1g of halloysite nanotubes, 0.18g of CsPbCl is encapsulated in the composite material1.5 Br 1.5 Perovskite quantum dots.
[0123] Take toluene and polystyrene at a volume (mL) and mass (g) ratio of 10:1, mix well, and stir magnetically to dissolve the polystyrene completely to obtain a polystyrene solution. 0.1 g CsPbCl is required for 100 mL of polystyrene solution. 1.5 Br 1.5 @HNT-Br-F material ratio, respectively take polystyrene solution and Cs PbCl 1.5 Br 1.5 @HNT-Br-F. CsPbCl 1.5 Br 1.5 The HNT-Br-F material was dispersed in a polystyrene solution and after magnetic stirring for 6-12 hours, a water-resistant and light-heat-resistant perovskite-based composite light conversion film was prepared using the Myler rod coating technique.
[0124] The fluorescence image of the perovskite-based composite light conversion film prepared in this embodiment and the overlapping image of the plant chlorophyll and photosynthetic system reaction center are shown in FIG. Figure 4 As shown, from Figure 4 It can be seen from a that it has a good overlap with the absorption of chlorophyll and photosynthetic system reaction center of plants, so it can be used as a light conversion film for plant photosynthesis.
[0125] The perovskite-based composite light conversion film prepared in this embodiment has an effect on the chlorophyll content of plants after irradiation. Figure 5 As shown, from Figure 5 It can be seen that the plants irradiated by the perovskite-based composite light conversion film have a higher chlorophyll content, indicating that the light conversion film material is beneficial to promoting plant photosynthesis.
[0126] Example 5
[0127] Take oleic acid and octadecene at a volume ratio of 1:2, mix well, and obtain the first mixed solvent. Add 2.5mmol cesium carbonate and 1mmol oleylamine to 100mL of the first mixed solvent, heat to 120℃ under nitrogen atmosphere to completely dissolve cesium carbonate, and keep warm for 2h to evaporate the low boiling point solvent. Heat to 150℃ again, and carry out coordination exchange reaction for 2.5h. After the reaction is complete, cool naturally to room temperature to obtain brown waxy solid cesium oleate.
[0128] Dimethyl sulfoxide and anhydrous ethanol were taken at a volume ratio of 1:1, mixed to obtain a third mixed solvent; the third mixed solvent and lead bromide were taken at a ratio of 0.5mmol lead bromide added to 10mL of the third mixed solvent; lead bromide was added to the third mixed solvent, and magnetic stirring was performed to completely dissolve the lead bromide to obtain a mixed solution. HNT was added to the mixed solution at a ratio of 1.0g HNT added to 100mL of the mixed solution, and the temperature was raised to 120°C after ultrasonic treatment for 5h until it was completely dried, so that the lead bromide was encapsulated in the tube of the HNT to obtain a product, and the product was washed at least three times with the third mixed solvent to obtain the PbBr2@HNT material.
[0129] Subsequently, cesium oleate was added to the third mixed solvent, and magnetic stirring was performed to completely dissolve the cesium oleate to obtain a cesium oleate solution with a molar concentration of 50 mM. According to the ratio of 10 mL of cesium oleate solution and 0.5 g of PbBr2@HNT material required for 100 mL of anhydrous toluene, anhydrous toluene, cesium oleate solution and PbBr2@HNT material were taken respectively, and the PbBr2@HNT material was dispersed in the cesium oleate solution, magnetically stirred for 1 hour, added to anhydrous toluene, and magnetically stirred for another 0.5 hour, filtered, separated, washed and dried to obtain a halloysite-perovskite (CsPbBr3@HNT) composite material. Among them, according to 1 g of halloysite nanotubes, 0.17 g of CsPbBr3 perovskite quantum dots were encapsulated in the composite material.
[0130] Toluene and polystyrene were taken at a volume (mL) and mass (g) ratio of 10:1, mixed, and magnetically stirred to completely dissolve the polystyrene to obtain a polystyrene solution. Polystyrene solution and CsPbBr3@HNT were taken at a ratio of 0.1gCsPbBr3@HNT material per 100mL polystyrene solution. CsPbBr3@HNT material was dispersed in the polystyrene solution, magnetically stirred for 6-12h, and then the perovskite-based composite light conversion film was prepared by Mehler rod coating technology.
[0131] The perovskite-based composite light conversion film prepared in this embodiment has weak fluorescence performance because the internal halogen functional groups are not modified.
[0132] The preferred embodiments of the present application are described in detail above, but the present application is not limited thereto. Within the technical concept of the present application, the technical solution of the present application can be subjected to a variety of simple modifications, including combining various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed in the present application and belong to the protection scope of the present application.
Claims
1. A composite fluorescent material comprising halloysite nanotubes and cesium lead halide perovskite quantum dots encapsulated in the halloysite nanotubes; in, The inner surface of the halloysite nanotube is grafted with a halogen ligand represented by formula I, ; In formula I, X1 is selected from chlorine, bromine or iodine, and R1 is selected from C2-C6 alkylene; The outer surface of the halloysite nanotube is grafted with a fluorosilicone ligand represented by formula II, ; In formula II, R2, R3 and R4 are the same or different and are independently selected from C1-C4 alkyl groups, and R5 is selected from C1-C4 alkylene groups or fluorine-substituted C1-C4 alkylene groups.
2. The composite fluorescent material according to claim 1, characterized in that: The halogen ligand is selected from one or more of (3-bromopropyl)phosphoric acid, ethephon, 6-bromohexanephosphoric acid and 4-bromobutanephosphoric acid; The fluorosiloxane ligand is selected from one or more of trifluoropropanetrimethoxysilane, triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane, 3,3,3-trifluoropropyltriethoxysilane and (3,3,4,4,5,5,5-heptafluoropentyl)trimethoxysilane.
3. The composite fluorescent material according to claim 1 or 2, characterized in that: The cesium lead halide perovskite quantum dots are selected from CsPbCl3 perovskite quantum dots, CsPbBr3 perovskite quantum dots, CsPbI3 perovskite quantum dots, CsPbCl 1.5 Br 1.5 Perovskite quantum dots, CsPbCl 1.5 I 1.5 Perovskite quantum dots and CsPbBr 1.5 I 1.5 One or more of perovskite quantum dots; and / or The mass ratio of the cesium lead halide perovskite quantum dots to the halloysite nanotubes is (0.1-0.5):
1.
4. The composite fluorescent material according to claim 1 or 2, characterized in that: The mass ratio of the cesium lead halide perovskite quantum dots to the halloysite nanotubes is (0.15-0.3):
1.
5. A method for preparing a composite fluorescent material according to any one of claims 1 to 4, comprising the following steps: S1: performing a third reaction on the halloysite nanotubes and the lead halide to obtain a third reaction product, S2: performing a fourth reaction on the third reaction product of step S1 and the cesium oleate solution to obtain the composite fluorescent material; Wherein, the halloysite nanotube is selected from the halloysite nanotube HNT-XF modified by the halogen ligand shown in formula I and the fluorosilicone ligand shown in formula II, ; In formula I, X1 is selected from chlorine, bromine or iodine, R1 is selected from C2-C6 alkylene, ; In formula II, R2, R3 and R4 are the same or different and are independently selected from C1-C4 alkyl groups, and R5 is selected from C1-C4 alkylene groups or fluorine-substituted C1-C4 alkylene groups.
6. The preparation method according to claim 5, characterized in that: The preparation of the halloysite nanotube HNT-XF comprises the following steps: Step A: performing a first reaction on the halloysite nanotube and the halogen ligand shown in Formula I to obtain the halloysite nanotube HNT-X modified with the halogen ligand; Step B: The halloysite nanotube HNT-X prepared in step A is subjected to a second reaction with the fluorosiloxane ligand shown in formula II to obtain the halloysite nanotube HNT-XF modified with the halogen ligand and the fluorosiloxane ligand.
7. The preparation method according to claim 5, characterized in that: The halogen ligand is selected from one or more of (3-bromopropyl)phosphoric acid, ethephon, 6-bromohexanephosphoric acid and 4-bromobutanephosphoric acid; The fluorosiloxane ligand is selected from one or more of trifluoropropanetrimethoxysilane, triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane, 3,3,3-trifluoropropyltriethoxysilane and (3,3,4,4,5,5,5-heptafluoropentyl)trimethoxysilane.
8. The preparation method according to any one of claims 5 to 7, characterized in that: In step S1, the lead halide is selected from one or more of PbCl2, PbBr2 and PbI2; and / or In step S1, the ratio of the mass of the halloysite nanotubes to the molar amount of the lead halide is (0.01-0.5) g:1 mmol; and / or In step S1, the third reaction is carried out in a mixed solvent of dimethyl sulfoxide and anhydrous ethanol; and / or In step S2, the ratio of the mass of the third reaction product to the molar amount of cesium oleate in the cesium oleate solution is (0.1-3) g:1 mmol; and / or In step S2, the solvent in the cesium oleate solution is selected from a mixed solvent of dimethyl sulfoxide and anhydrous ethanol, and the molar concentration of cesium oleate in the cesium oleate solution is 50 mM-100 mM; and / or In step S2, the fourth reaction is carried out in toluene solvent.
9. The preparation method according to claim 8, characterized in that: In step S1, the ratio of the mass of the halloysite nanotubes to the molar amount of the lead halide is (0.04-0.4) g:1 mmol; and / or In step S2, the ratio of the mass of the third reaction product to the molar amount of cesium oleate in the cesium oleate solution is (0.25-1) g:1 mmol.
10. The preparation method according to claim 6, characterized in that In step A, the ratio of the mass of the halloysite nanotubes to the molar amount of the halogen ligand is (100-1000) mg:1 mmol; and / or In step A, the first reaction is carried out in a mixed solvent of anhydrous ethanol and water; and / or In step A, the temperature of the first reaction is 5°C-35°C, and the time of the first reaction is 5 days-9 days; and / or In step B, the ratio of the mass of the halloysite nanotube HNT-X to the molar amount of the fluorosilicone ligand is (0.01-10) g:1 mmol; and / or In step B, the second reaction is carried out in toluene solvent; and / or In step B, the temperature of the second reaction is 60°C-100°C, and the time of the second reaction is 12h-36h.
11. The preparation method according to claim 10, characterized in that: In step A, the ratio of the mass of the halloysite nanotubes to the molar amount of the halogen ligand is (200-500) mg:1 mmol.
12. Use of the composite fluorescent material according to any one of claims 1 to 4 or the composite fluorescent material prepared by the preparation method according to any one of claims 5 to 11 in a light emitting diode or a light conversion film.
13. A perovskite-based composite light conversion film, comprising the composite fluorescent material according to any one of claims 1 to 4 or the composite fluorescent material prepared by the preparation method according to any one of claims 5 to 11.
14. The perovskite-based composite light conversion film according to claim 13, characterized in that: The perovskite-based composite light conversion film also includes a polymer, and the mass ratio of the composite fluorescent material to the polymer is 1:(10-200).
15. The perovskite-based composite light conversion film according to claim 14, characterized in that: The mass ratio of the composite fluorescent material to the polymer is 1:(50-150).